2016
DOI: 10.1093/jme/tjw182
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating the Adaptation Process of Sandfly Fauna to Anthropized Environments in a Leishmaniasis Transmission Area in the Brazilian Amazon

Abstract: Phlebotomines (Diptera: Psychodidae) are vectors of several etiological agents of human and animal diseases, including protozoans of the gender Leishmania. Precarious socioeconomic conditions and uncontrolled population growth directly influence the transmission risk of parasites and the urbanization of vector species, previously restricted to wild environments. The Marajó Archipelago is considered a high incidence area of leishmaniasis in the Brazilian Amazon. However, it is poorly studied. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
3
7
0
2
Order By: Relevance
“…On WE1, we found the highest proportion of males, compared to females. The higher proportion of males in the population have been previously reported and this corroborates the results obtained in studies involving sampling of phlebotomines using light trap (Dye et al 1991, Barata et al 2004, Rosario et al 2017. For example, male sand flies are attracted to plants as a source of sugar meals.…”
Section: Discussionsupporting
confidence: 86%
“…On WE1, we found the highest proportion of males, compared to females. The higher proportion of males in the population have been previously reported and this corroborates the results obtained in studies involving sampling of phlebotomines using light trap (Dye et al 1991, Barata et al 2004, Rosario et al 2017. For example, male sand flies are attracted to plants as a source of sugar meals.…”
Section: Discussionsupporting
confidence: 86%
“…Despite high overall species diversity, numerical domination (74.8%) of only three species was expected. Studies on forested environments have shown a phlebotomine fauna generally composed of a few dominant species and many species with few specimens [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In certain cases, sandflies could adapt quickly to new environments. Rosário et al (2017) documented that several New World sandfly species were adapted to the urbanised regions of Brazil in the last few decades. However, it should be noted that warmer, nutrient-rich and predator-poor habitats provided by cities are favoured by sandfly species.…”
Section: Discussionmentioning
confidence: 99%